Determinants of child body weight categorization in parents and health care professionals: an experimental study - Evans, Elizabeth H.; Ridley, Bethany J.; Cornelissen, Piers L.; Kramer, Robin S. S.; Araújo-Soares, Vera; Tovée, Martin J. (British journal of health psychology, 2025)
Objectives Parents infrequently recognize childhood overweight/obesity and healthcare professionals (HCPs) also struggle to visually identify it, potentially limiting the offer and uptake of weight management support. This study examined perceptual and attitudinal/cognitive determinants of child weight judgements amongst parents and HCPs to identify targets for intervention. Design We used a mixed experimental design with parents and HCPs as the between-participants factor. Stimulus gender, age and BMI centile were the within-participant repeated measures factors. Methods One hundred and fifty-six HCPs and 249 parents of children aged 4-5 or 10-11 years viewed simulated child images. They estimated their relative size and categorized the weight status of each figure. Stimuli were photo-realistic figural scales based on 3D-scans of 4- to 5- and 10- to 11-year-old children varying in adiposity. Participants also reported their beliefs about causes, controllability and categorization of child weight. Results Both groups accurately estimated the figures' relative size. However, categorization of higher weight figures was poor, demonstrating a mismatch between perceptual judgements of size and categorization of weight status. Lower levels of comfort with assigning ‘overweight’ categorizations to children, and a stronger belief that weight was controllable by the child/parent, predicted less accurate weight status categorizations. Conclusions Parental and HCP misperceptions when categorizing children's higher weight are related to attitudinal/cognitive factors, including reluctance to label a child's weight status as overweight and beliefs about whether a child's weight can be controlled by them or their family.
Erstmals veröffentlicht: 14. November 2024
Gesehen am 29.04.2025